Requirement Model for POLIMAS Examination Evaluation System (PEES) - Amyzah, Ahmad (2006)
Requirements play an important role in system development project. It is because requirement forms the backbone of any successful project and provides the measure of success or failure of a certain project. Misinterpretation of the requirements would increase cost and hinder the system development to meet users’ expectation. Therefore, it is necessary to present the requirement in an understandable and meaningful way. This is achieved through requirement model. The model will give a complete view of certain system and represent idea without having to develop an n actual system. This research aims to create a requirement model for POLIMAS Examination Evaluation System (PEES). UML notation is used to model out the requirements. System modeling and horizontal prototype are used to validate the users’ requirements. Requirement model is validated by using system requirements testing, horizontal prototype and n test case. UML diagrams and a set of requirements list will be produced in this research. Several recommendations for future research will be discussed at the end of this research.